STATE FINANCIAL SUPPORT AS A MEANS OF PROMOTING AGRICULTURAL COOPERATIVES - Vardanyan, Artur (State and Law, 2020)
The article analyzes the legal nature of the types of state financial support to agricultural cooperatives.. The article also indicates the problems of the current regulation in legal acts, indicates international practice and legal concepts of types of state financial support in the agricultural sphere in different EU countries, as well as in the United States and other countries.  Realizing the importance of new legal regulations, we have proposed a number of concepts aimed to improving the efficiency of legal regulation of financial support mechanisms.
Keywords: cooperative, state support, financial support, subsidy, subvention